Biodiversity of Koshi Tappu Wildlife Reserve: a post flood assessment - Khatri, Top B; Shah, Deep Narayan; Shah, Ram Devi Tachamo; Mishra, Nilamber (Journal of Wetlands Ecology, 2011)
Koshi Tappu Wildlife Reserve and its associated wetlands including Saptakoshi River are important wetland habitats for the critically endangered Wild Water Buffalos (Bubalus bubalis arnee), Migratory Birds and River Dolphins (Platanista gangetica). Rapid and complete inundation of the Reserve during monsoon and frequent changes in river courses almost every year has been the biggest threat to the existence of wild buffalo (locally known as 'Arna') and other wildlife. The breach of eastern embankment of the Koshi barrage at Kusaha of Sunsari district on 18th August 2008, created havoc for wildlife and their habitats, people’s livelihood and welfare. A study was therefore conducted to ascertain the status of biodiversity within Koshi Tappu Wildlife Reserve and its Buffer Zone from March to November 2009 to come up with the status of Arna, dolphins, marsh mugger crocodile, Swamp francolin (Simtitra), and vulture population and assess the ecological status of wetlands. Direct count method, transect method, point counts, qualitative samplings, field observation and social survey were carried out to study the biodiversity status. A total of 219 wild water buffalo, 11 dolphins, 5 marsh mugger crocodiles, 52 to 74 Swamp francolin and 517 vultures. The studied wetlands were moderately polluted. Altogether 42 taxa of benthic macro invertebrates were recorded. The results were further compared with a few years of data before the flood occurrence. The current result showed an encouraging population of key species at the Reserve but the threats for conservation still remain challenging. Key words: biodiversity; critically endangered; human pressure; Koshi breach; stewardship; wetlands DOI: 10.3126/jowe.v4i0.3734 Journal of Wetlands Ecology, (2010) Vol. 4, pp 69-82